Collapse Analysis of a Transmission Tower-Line System Induced by Ice Shedding - Li, Jiaxiang; Wang, Biao; Sun, Jian; Wang, Shuhong; Zhang, Xiaohong; Fu, Xing (Frontiers in Physics, 2021)
Ice shedding causes transmission lines to vibrate violently, which induces a sharp increase in the longitudinal unbalanced tension of the lines, even resulting in the progressive collapse of transmission towers in serious cases, which is a common ice-based disaster for transmission tower-line systems. Based on the actual engineering characteristics of a 500 kV transmission line taken as the research object, a finite element model of a two-tower, three-line system is established by commercial ANSYS finite element software. In the modeling process, the uniform mode method is used to introduce the initial defects, and the collapse caused by ice shedding and its influencing parameters are systematically studied. The results show that the higher the ice-shedding height is, the greater the threat of ice shedding to the system; furthermore, the greater the span is, the shorter the insulator length and the greater the dynamic response of the line; the impact of ice shedding should be considered in the design of transmission towers.